The Impact of Social Media on Youth Fashion Consumption: Trends, Influencers, and Ethical Shifts - Darshan Darshan; Akshat Soni; Aditya Godara; Yash Rangani; Milan Dhupper; Rahul Chauhan; Andino Maseleno (Greenation Research & Yayasan Global Resarch National, 2024)
This study explores the influence of social media on the fashion preferences and purchasing behaviors of young consumers, with a focus on platforms like Instagram, TikTok, and YouTube. Social media serves as a primary source of inspiration, shaping not only fashion trends but also how young people express their identities and engage with brands. The research highlights the significant role of influencers, user-generated content, and interactive brand-consumer engagements in shaping youth fashion consumption. Additionally, sustainability and ethical fashion choices are increasingly important to young consumers, with social media providing a platform for raising awareness and encouraging responsible consumerism. The findings, based on demographic analyses (age and gender), reveal that both factors do not significantly influence participants' perceptions of social media’s impact on fashion-related behaviors, suggesting a broad, consistent effect across different demographic groups. The study provides insights into how digital platforms have revolutionized fashion marketing, empowering young consumers to make informed and socially conscious fashion choices. The research underscores the need for further exploration into how these dynamics evolve over time and across different cultural contexts, particularly with regard to niche fashion communities and the role of influencers in driving change.